MOL Making Training for Litter Composting in Youth Organization of Kertonatan Village - Septi Aprilia Septi; Dodik Luthfianto Dodik; Elsa Sari Hayunah Nurdiniyah Elsa; Dian permatasari kusuma dayu (Peneliti Teknologi Teknik Indonesia, 2023)
The use of fertilizers in the world continues to increase along with the increase in population and consumption of agricultural production. Among the available fertilizers, compost is one environmentally friendly fertilizer type. Compost is fertilizer derived from organic materials such as leaves, straw, reeds, trash, grass and other similar materials. The advantages of compost are that it is free of wild plant seeds, free from pathogenic bacteria, easy to use, and provides a variety of nutrients plants need. In making compost, local microorganism starters are required to supply nutrients and as components responsible for maintaining optimal plant growth processes. Therefore, training is required on making local microorganism starters for composting litter waste into compost. Training will be given to youth organizations in Kertonatan Village to increase knowledge and skills in making MOL starters. The method provides technical material about making a liquid starter and direct practice with the audience. As a result, the participants received knowledge and direct practice regarding manufacturing liquid starter (MOL) and litter composting. The training for making Local Microorganism starters for composting litter for youth organizations in Kertonatan Village went smoothly.